Bacterial Multiresistance and Microbial Diversity of Milk Received by a University Hospital Milk Bank - Dayane da Silva Zanini; Benedito Donizete Menozzi; Wanderson Sirley Reis Teixeira; Felipe Fornazari; Gismelli Cristiane Angeluci; Raquel Cuba Gaspar; Lucas Franco Miranda Ribeiro; Carlos Eduardo Fidelis; Marcos Veiga dos Santos; Juliano Gonçalves Pereira; Helio Langoni (Microorganisms)
Breastfeeding is fundamental for the development and protection of the newborn, and microorganisms present in breast milk are associated with the development of the infant’s intestinal microbiota. However, there are factors that interfere with breastfeeding, resulting in the need to supply donated milk to milk banks for these children. Even though there is a restriction on medications prescribed for pregnant and breastfeeding women, some antimicrobials are accepted, as long as they are used correctly and as they can increase the selection pressure for resistant bacteria. The microorganisms present in breast milk from a human milk bank were evaluated and the resistance of the isolates to antimicrobials was phenotypically characterized. In total, 184 microbial isolates were identified by mass spectrometry, of 12 bacterial genera and 1 yeast genus. There was a high prevalence of bacteria of the genus Staphylococcus, mainly S. epidermidis (33%). Resistance to antimicrobials varied among species, with a higher percentage of isolates resistant to penicillins and macrolides. Multidrug resistance was identified in 12.6% of 143 isolates. Breast milk contains a wide variety of microorganisms, mainly those of the Staphylococcus and Enterobacter genera. There was a high percentage of resistant isolates, and multidrug resistance in Klebsiella oxytoca (66.7%; 4/6) and S. epidermidis (15.0%; 9/60) isolates, which increases the public health concern.